Patch testing hydroxyethyl (meth)acrylate. (1st October 2019) - Rolls, S.; Chowdhury, M.M.; Cooper, S.; Cousen, P.; Flynn, A.M.; Ghaffar, S.A.; Green, C.M.; Haworth, A.; Holden, C.; Johnston, G.A.; Naidoo, K.; Orton, D.I.; et al.
Summary: Contact allergy occurs when the skin comes into contact with allergens (chemicals that cause allergy), causing sensitisation. This means that if the skin comes into contact with the same allergen again, it can develop an eczema‐like reaction known as allergic contact dermatitis (ACD), which affects 20% of people. Patch testing is used by dermatologists to find out what the substance causing the reaction might be. This is done by applying a range of known allergens to patches of the skin to see which trigger a reaction. The baseline (standard) series of patch test allergens is recommended in everyone undergoing patch testing and aims to include the most common allergens which cause ACD. (Meth)acrylate chemicals are the key ingredients in acrylic nails, gel nails and gel polish nails. There are different types of meth(acrylates). The authors of this study from 15 centres in the U.K. decided to add 2‐hydroxyethyl methacrylate (2‐HEMA) 2% in petrolatum (pet.) to the baseline patch test series in 2016‐7, aiming to detect ACD in patients using acrylic nails. Patients with a history of (meth)acrylate exposure, or who tested positive to 2‐HEMA, were then selectively tested with a further short series of eight (meth)acrylate allergens. Of 5, 920 patients, 1.7% (102) were allergic to 2‐HEMA and 2.4% (140) to at least one (meth)acrylate. (Meth)acrylate allergy would have been missed in 0.6% of patients (36) without testing 2‐HEMA in everyone. 94% of allergic patients were women. 37 of the 140 were sensitised by working in the nail industry and 97 were sensitised by wearing acrylic nails. Only six people developed the allergy due to exposure to other sources (surgical glue, adhesive medical appliances and printing ink). The authors recommend that 2‐HEMA 2% pet. should be added to the British baseline patch test series and suggest a standardised short series of 15 (meth)acrylate chemicals, which is likely to detect most cases of (meth)acrylate allergy.